Solid-Gas Coupling Model for Coal-Rock Mass Deformation and Pressure Relief Gas Flow in Protection Layer Mining. (2nd April 2018) - Zhu, Zhuohui; Feng, Tao; Yuan, Zhigang; Xie, Donghai; Chen, Wei
Abstract : The solid-gas coupling model for mining coal-rock mass deformation and pressure relief gas flow in protection layer mining is the key to determine deformation of coal-rock mass and migration law of pressure relief gas of protection layer mining in outburst coal seams. Based on the physical coupling process between coal-rock mass deformation and pressure-relief gas migration, the coupling variable of mining coal-rock mass, a part of governing equations of gas seepage field and deformation field in mining coal-rock mass, is introduced. Then, a new solid-gas coupling mathematical model reflecting the coupling effects of gas adsorption/desorption, gas pressure, and coal-rock mass deformation on the mining coal-rock mass deformation and pressure relief gas flow is established combined with the corresponding definite conditions. It lays a theoretical foundation for the numerical calculation of the deformation of mining coal-rock mass and the migration law of gas under pressure relief in the outburst coal seam group.